Analysis of cognitive skills required from candidate accountants in the brazilian Federal Public Administration, using indicators based on Bloom's Taxonomy - Santana Junior, Jorge José Barros de; Pereira, Dimmitre Morant Vieira Gonçalves; Lopes, Jorge Expedito de Gusmão (Revista Contabilidade & Finanças, 2008)
This study aims to detect, by means of the six knowledge levels in Bloom´s Taxonomy, tendencies in the cognitive abilities required when professional accountants are demanded by the Brazilian Direct and Indirect Administration, using the analysis of questions posed during some recent selection exams (1999 to 2006), to evidence the intellectual performance profile outlined by the public sector. Based on this analysis, attempts are made to reflect on future measures to allow professional accountants to comply with the intellectual performance demands posed by the current global technological and economic development scenario. The article was developed using the inductive method, through bibliographical and documental research, besides statistical research techniques. The history of the last changes occurred in the professional market is addressed, particularly in the public sector, as well as the understanding of the fundamentals of Bloom´s Taxonomy, proposing some learning indicators more directed at current reality. O resultado da pesquisa demonstrou que não se está exigindo dos candidatos ao cargo de contador (ou com especialidade em contabilidade) os mais altos indicadores de habilidades cognitivas. Verifica-se, portanto, a necessidade de mudanças efetivas nos rumos dessa profissão, para que se possa garantir o espaço almejado para todos aqueles que optaram em trabalhar e desenvolver as Ciências Contábeis. The research results showed that the highest cognitive skill indicators are not being demanded from candidate accountants (or with a specialization degree in accountancy). The need for effective changes are needed in where this profession is heading, in order to guarantee the space wanted by everybody who chose to work in and develop Accountancy.